An overview of study designs. (2nd May 2020) - Aquilina, Julian; Neves, Joana B; Tran, Maxine GB
Abstract : The numbers of clinical trials have increased exponentially over the last decade, amplifying the pressure to select an appropriate study design to obtain reliable and valid evidence. The ability to find, critically appraise and use evidence to develop new interventions is fundamental to evidence-based medicine. Different study designs have their own advantages and disadvantages, and provide different evidentiary value. This article provides an overview of clinical trials, illustrating that, ultimately, the study design chosen needs to meet experimental and funding limitations, while minimising error.